The status of clinic committees in primary level clinics in three provinces in South Africa - Padarath, Ashnie Pooran (University of the Western Cape, 2014)
Magister Public Health - MPH === In South Africa, governance structures in the form of clinic committees, hospital boards and district health councils are intended to provide expression to the principle of community participation at a local and district level. They are meant to act as a link between communities and health services and to provide a conduit for the health needs and aspirations of the community to be represented at various local, districts, provincial and national levels. This study aimed to assess the functioning of health governance structures in the form of clinic committees. Specifically, the study sought to ascertain the number of clinic committees associated with public health facilities in three provinces in South Africa namely the Eastern Cape, Free State and KwaZulu Natal and to identify the factors that are perceived by clinic committee members to either facilitate or impede the effective functioning of clinic committees. === South Africa